Survival street ebook - Asmus, James (Survival Street., 2023)
Survival Street is a unrepentant action satire tearing through a dystopia packed with economic and humanistic cautionary tales.After an unbridled wave of corporations take over America, the country is left completely deregulated and effectively carved up into feudal states where billionaires and businesses make their own laws. Among the wreckage, mass privatization shuts down public broadcasting forcing all the beloved edu-tainers out on the down and dirty streets. One group of them stick together, determined to keep helping kids across the country and do it by becoming an A-Team-esque band of mercenaries fighting for (and educating!) kids in the crumbling, corporate war zone of New Best America.A candy coating of pop culture madness, humor, cartoonishly absurd hyper-violence, and just enough hope to keep holding on. Collects Survival Street #1–#4.